HUMAN RESOURCE OUTSOURCING: A NEW OPPORTUNITY FOR ORGANIZATION - Mangaleswaran, T.; Srinivasan, P.T. (University of Madras, 2006)
Today most of the organizations are outsourcing their human resource operations to complete in the market. They have understood it as the way to minimize the cost and enhance the productivity of organization to complete in the market. It is the huge opportunity to the vendors or suppliers of Human Resource as well as to the clients. It is the fastest growing segment within the Business process outsourcing. Human Resource outsourcing provides knowledge and competencies to the organization. At present all organizations think enhancing their market capitalization via intellectual capital, which is lacking or rare or not available-, in house in some organizations. Human Resource Outsourcing (HRO) is the only way to fulfill their requirement. As a result, organizations are now considering HR outsourcing as a viable option and it is a business. This paper discusses the meaning of HRO, reasons for outsourcing and categorizes the areas to be outsourced; the paper also lists out the advantages and disadvantages of HRO in organization. It further looks at the problems involved in outsourcing and how to take outsourcing decision. Finally this paper discusses the HRO in Indian context.